Inhibition of potential thyroperoxidase (tpo) by mangifera indica l. Leaves extract - Sharmiladevi A/P Sinaiyah (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
There are numerous ways to treat the hyperthyroidism using modern medication such as consumption of synthetic anti-thyroid drugs (ATD), surgery, and radioactive iodine treatment. These treatment bring negative side effect to the patient. Therefore, in this research, the natural way to treat the hyperthyroidism, which is by inhibiting the thyroperoxidase (TPO) enzyme using Mangifera indica L. leaves extracts will be studied. This study is conducted by experimenting five types of extraction method which are Hot maceration, Cold maceration, Ultrasonic extraction, and Soxhlet extraction. The total flavonoid content (TFC) is determined from the aluminium colorimetric method, and it is found out that the Soxhlet extraction's M. indica L. leaves extracts yields the highest which is 30.00 0.008 mgIQE/g. Therefore, the best extraction method for the extraction of M. indica L. leaves is by Soxhlet extraction. The TPO activity inhibition is analysed using computerized UV-VIS spectrophotometer. About 15 g/ml of TPO enzyme is used analyse TPO iodide-oxidation activity. The highest TPO iodide-oxidation activity inhibition is found by Soxhlet extraction's extracts which is 92.07%. The result show the correlation between the high TFC and the high inhibition of TPO iodide-oxidation. The inhibitory concentration, 〖IC〗_50 of the Soxhlet extraction's extracts is found out to be 0.0063g/ml. Therefore, Soxhlet extraction has been found to be best extraction method for M. indica L. leaves extract, for the inhibition of TPO iodide-oxidation activity.